Outdoor pollen concentration is not associated with exercise‐induced bronchoconstriction in children - Tikkakoski, Anna P.; Karjalainen, Jussi; Sipilä, Kalle; Kivistö, Juho E.; Kähönen, Mika; Lehtimäki, Lauri; Tikkakoski, Antti (Pediatric pulmonology, 2022)
Background Free running exercise test outdoors is an important method to diagnose asthma in children. However, the extent of how much exposure to pollens of outdoor air affects the results of the test is not known. Methods We analyzed all reliable exercise challenge tests with impulse oscillometry in children (n = 799) between January 2012 and December 2014 in Tampere University Hospital. Pollen concentrations at the time of the test were collected from the register of Biodiversity Unit of the University of Turku. We compared the frequency of exercise‐induced bronchoconstriction and pollen concentrations. Results The analyses were restricted to birch and alder pollen as high counts of grass and mugwort pollen were so infrequent. The relative change in resistance at 5 Hz after exercise or the frequency of exercise‐induced bronchoconstriction were not related to alder or birch pollen concentrations over 10 grains/m3 (p = 0.125–0.398). In logistic regression analysis comparing the effects of alder or birch pollen concentrations, immunoglobulin E (IgE)‐mediated alder or birch allergy and absolute humidity over 10 g/m3 only absolute humidity was independently associated with change in airway resistance (odds ratio [OR]: 0.32, confidence interval [CI]: 0.13–0.67, p: 0.006). Conclusions In our large clinical sample, outdoor air pollen concentration was not associated with the probability of exercise‐induced bronchoconstriction in free running test in children while low absolute humidity was the best predictor of airway obstruction.